2010
DOI: 10.1179/146532810x12637745451951
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide poisoning caused by ingestion of apricot seeds

Abstract: Cyanide poisoning associated with ingestion of apricot seeds is an important poison in children, many of whom require intensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 15 publications
2
36
0
14
Order By: Relevance
“…The amygdalin content of stone fruit seeds could produce cyanide in the range of 0.01 -1.1 mg cyanide equivalents/g; this value is relatively high. Thus, ingestion of the kernels either intentionally or accidentally could result in acute or sub-acute health problems (Akyildiz, Kurtoğlu, Kondolot, & Tunç, 2010;Cigolini, Ricci, Zannoni, Codogni, Luca, Perfetti, & Giampaolo, 2011) especially if taking place over prolong periods of time.…”
Section: Amygdalin Contents Of Seeds From Rosaceae Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The amygdalin content of stone fruit seeds could produce cyanide in the range of 0.01 -1.1 mg cyanide equivalents/g; this value is relatively high. Thus, ingestion of the kernels either intentionally or accidentally could result in acute or sub-acute health problems (Akyildiz, Kurtoğlu, Kondolot, & Tunç, 2010;Cigolini, Ricci, Zannoni, Codogni, Luca, Perfetti, & Giampaolo, 2011) especially if taking place over prolong periods of time.…”
Section: Amygdalin Contents Of Seeds From Rosaceae Speciesmentioning
confidence: 99%
“…Failure to minimise exposure to amygdalin (and, consequently, hydrogen cyanide) could result in acute and sub-acute health problems to consumers (Shragg, Albertson, & Fisher, 1982;Akyildiz et al, 2010).…”
Section: Amygdalin Contents Of Non-rosaceae Seedsmentioning
confidence: 99%
“…These include apricot seeds [2][3][4][5][6][7][8][9][10], cassava -the tapioca root consumed commonly as sago [11], peaches [10,12], flax seeds [13], bitter almonds [14] apple seeds [10], cherry [15,16], papayas, lima beans, clover and sorghum [17]. Human body has built in metabolic mechanisms capable of detoxifying small quantities of cyanide ingested.…”
Section: Discussionmentioning
confidence: 99%
“…The oxalate content obtained from this work suggested that, it could be safe for consumption as far as it oxalates content was concerned since it fell below the lethal dose limit. High level of cyanide in foods has been implicated with cerebral damage and lethargy in man and his animals [21] although most levels of this substance are generally regarded to be highly toxic to animals. NRC, [22] gave the toxic level to be between the range of 50 to 200mg/100g.…”
Section: Anti-nutritional Propertiesmentioning
confidence: 99%